(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
Spring wheat is a significant crop in Latvia. The fertilisation influences the crop yield and the quality greatly.The main task of experiments: to test the effect of micronutrients (DDMn) and macronutrients (Phosific) supplied through leaves for the modeling environment protecting high yield and grain quality technology’. The grain yield, the quality and the physiological activity were detected.The mineral supply through leaves during the wheat heading phase increased yield for more than 0.2 - 0.4 t ha'1 in comparison with the control. The physiological activity of grains is higher, but there is no significant influence on the quality of grains.